2011
DOI: 10.1103/physrevc.83.035802
|View full text |Cite
|
Sign up to set email alerts
|

New equation of state for astrophysical simulations

Abstract: We generate a new complete equation of state (EOS) of nuclear matter for a wide range of temperatures, densities, and proton fractions ready for use in astrophysical simulations of supernovae and neutron star mergers. Our previous two papers tabulated the EOS at over 180,000 grid points in the temperature range T = 0 to 80 MeV, the density range nB = 10 −8 to 1.6 fm −3 , and the proton fraction range YP = 0 to 0.56. In this paper we combine these data points using a suitable interpolation scheme to generate a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
271
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(281 citation statements)
references
References 20 publications
9
271
0
1
Order By: Relevance
“…The QS approach gives the Beth-Uhlenbeck formula in the low density limit, but gives also a generalized Beth-Uhlenbeck formula which takes in-medium effects into account [40]. The virial EOS of G. Shen et al [31,32] uses also the correct second virial coefficient so that the chemical constants are reduced, but mean-field effects are not included consistently so that the results for the chemical constants remain near to the values of the ideal NSE case. An attempt to construct an EOS which treats simultaneously the virial coefficient and the mean-field contributions has been performed in Ref.…”
Section: E Qsmentioning
confidence: 99%
See 2 more Smart Citations
“…The QS approach gives the Beth-Uhlenbeck formula in the low density limit, but gives also a generalized Beth-Uhlenbeck formula which takes in-medium effects into account [40]. The virial EOS of G. Shen et al [31,32] uses also the correct second virial coefficient so that the chemical constants are reduced, but mean-field effects are not included consistently so that the results for the chemical constants remain near to the values of the ideal NSE case. An attempt to construct an EOS which treats simultaneously the virial coefficient and the mean-field contributions has been performed in Ref.…”
Section: E Qsmentioning
confidence: 99%
“…At highest den-sity, a sudden decrease of K c [α] occurs, which is probably due to the onset of the transition from the "virial regime" to the intermediate density regime without alpha particles. Note that the tabulated EOSs of G. Shen et al are based on a smoothing and interpolation procedure [31,32], which could explain why the transition between the two regimes is smoothed out and not abrupt.…”
Section: G Shen Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The SHT UU model consists of two NSs with gravitational mass of 1.4 M each, and employs the EOS by Shen, Horowitz, Teige (SHT, Shen et al 2010, Shen et al 2011. The initial NS spins are aligned with the orbital angular momentum, with dimensionless spin J/M 2 ≈ 0.125.…”
Section: Setup and Numerical Evolutionmentioning
confidence: 99%
“…The most frequently used EoS were developed by Lattimer and Swesty [6], based on the compressible liquid drop model and the non-relativistic Skyrme force , and by Shen et al, [7], who used the Thomas-Fermi (TF) approximation with a relativistic mean-field (RMF) model. Recently published new EoS for CCSN simulations [8,9] use the virial EoS at low density and Hartree RMF in both the inhomogeneous and uniform matter regions. Hempel et al [10] reported calculations based on the nuclear statistical equilibrium model, which includes excluded volume effects and RMF interactions.…”
mentioning
confidence: 99%